Cloning of the aroP gene and identification of its product in Escherichia coli K-12. - Chye, M L (1986)
The aroP gene of Escherichia coli K-12 was located in a ca. 1.2-kilobase region of DNA. The aroP gene product was identified as a membrane-bound protein with an apparent molecular weight of approximately 37,000.